Visual literacies in a U.S. undergraduate writing course: a case study of transmediation. Issue 1 (3rd April 2019) - Min, Jeeyoung
Abstract: This interpretive case study examines how undergraduate students enact visual literacies, focusing on transmediation from visual-embedded research papers into multimodal brochures, in an entry-level college writing course at a large research university in the U.S. Data sources included students' artifacts, interview transcripts, and field notes. A four-dimensional interpretation model for multimodal composing practices was used to analyze and interpret the data sources. Findings revealed that undergraduates shaped their understandings of multimodal representation of brochures through the process of noticing, conceptualizing, constructing, and conveying social meanings of multimodal assemblages. As iterating over the process through the six stages of teaching brochure composition in class, the undergraduates reshaped their multimodal understandings for a better representation and communication of multimodal social meanings of the brochures. The study has implications for the significance of the infusion of explicitly taught visual literacies into college preparatory writing for the growth and development of visual composers.